Enhancing energy absorption in quantum dot solar cells via periodic light-trapping microstructures. (1st August 2016) - Miller, Christopher Wayne; Fu, Yulan; Lopez, Rene
Abstract: Colloidal quantum dot (CQD) solar cells prove to be promising devices for optoelectronic applications due to their tunable absorption range, deep infrared absorption capabilities, and straightforward processability. However, there remains a need to further enhance their device performance—particularly when one has to adhere to strict physical limitations on their physical structure. Here we present a three-dimensional numerical model of CQD solar cells in COMSOL Multiphysics based on the finite element method. With this model we have simulated the optical characteristics of several CQD solar cells across varying photonic structures and physical parameters to investigate how distinct photonic structures may enhance the light absorption and current output of CQD solar cells using identical physical parameters. Of the many cells simulated, one notable model increased the predicted current in the active layer PbS by 69.33% as compared to a flat solar cell with identical physical parameters, and produced a current of 24.18 mA cm −2 by implementing a cross-shaped photonic structure built on top of a flat substrate of glass and ITO. This cross-shaped model serves as a key example of how unique photonic structures can be implemented to further enhance light absorption.